Examining maternal effects and genetic differentiation in P. flexilis and P. aristata to improve success of conservation actions - Borgman, Erin M., author; Hufbauer, Ruth, advisor; Schoettle, Anna, advisor; Angert, Amy, committee member; Steingraeber, David, committee member (Colorado State University. Libraries, 2013)
As the climate changes and invasive species continue to spread, proactive management may be needed to conserve native plant populations. Selecting appropriate plant material for restoration or other actions that will sustain populations is an integral part of any such plan and must take into account genetic differentiation to limit maladaptation. Common garden studies are used to determine the genetic basis of trait variation among populations from different geographic sources. However, maternal effects, the effect of environment during offspring development, can also affect performance, complicating the interpretation of these studies. Growing one generation in a common environment can help correct for maternal effects, but is often not practical with long-lived species. Using limber pine (Pinus flexilis) and Rocky Mountain bristlecone pine (Pinus aristata) as model species, I explored the contribution of maternal effects to early seedling growth among populations in a greenhouse common garden study. I grew offspring sourced over multiple years from the same mother trees, comparing growth traits between source years. Additionally, I collected five twig clippings from the upper canopy of each mother tree and measured characteristics indicative of the relative vigor of the tree during each seed source year. There were significant (p<0.05) differences in year-to-year variation in twig growth characteristics, seed size, and seedling performance. For bristlecone pine, there was a significant positive relationship between the relative inter-annual (RIA) variation in seed mass and seedling total dry mass and a negative relationship between the RIA variation in seed mass and needle growth at 210 days. For limber pine, there were significant positive relationships between RIA variation in seed mass and cotyledon length, stem height, stem diameter, and needle length at 20, 120, and 190 days. These results a) support the hypotheses that maternal effects are evident in both P. flexilis and P. aristata and that these effects translate into variation in early seedling growth and b) suggest possibilities for statistically correcting for maternal effects in genetic differentiation common garden studies involving long-lived species. Using these data I then conducted a common garden greenhouse study to determine the degree of genetic differentiation in limber pine populations in the Southern Rockies. Mid-summer precipitation varies greatly along a latitudinal gradient throughout this region, potentially selecting for local adaptation of populations to their native moisture regime. I evaluated the differential response of seed sources from northern and southern portions of the range to different moisture regimes during early seeding growth. To test whether seedling growth traits, which are often adaptive, differed between northern and southern seed sources, I measured primary needle length, stem diameter, water potential, and biomass allocation between root and shoot before, during, and after treatments. To test for differentiation in the adaptive traits associated with water use, I also measured carbon isotope ratios (δ13C) as a proxy for water use efficiency. To account for maternal effects I used cotyledon length as a covariate, which I found in the previous study to be a good indicator of maternal year-to-year variation in seedling growth. There were significant (p<0.05) effects of source region for root length, stem diameter, needle length, and total dry mass, where seedlings from southern sources were bigger than those from northern sources. Seedlings from the north had a higher probability of mortality than those from southern populations, as did seedlings in the dry treatment. The only significant interaction between growth response and source region, signifying the possibility of local adaptation of populations, was with the carbon isotope ratio (δ13C, p<0.1). All seedlings in the dry treatment regardless of origin had higher δ13C, while seedlings in the wet treatment varied between slightly higher (southern populations) and lower (northern populations) values of δ13C. These data indicate that genetic differentiation exists among populations in the Southern Rockies, potentially increasing the risk of maladaptation when moving seed far from its source.
Keywords: common garden; maternal effects; limber pine; genetic differentiation